Microstructure and Optical Properties of Transition Metal \((Co, Ni)\)-Doped \(TiO_2\) Nanowires Synthesized by Solvothermal Method - Hoa, Nguyen Thi Quynh; Hung, Luu Tien; Minh, Nguyen Thi; Nga, Le Thi Kieu; Quang, Nguyen Hong (Communications in Physics, 2012)
The undoped and transition metal (Co, Ni)-doped TiO\(_2\) nanowires were synthesized by simple and low cost solvothermal method and their microstructure and optical properties were investigated based on the fixed doping concentration of 1 at.%. The X-ray diffractometer and highresolution transmission electron microscopy demonstrated that the nanowire had a single-crystalline rutile structure and grew along the [001] growth direction. The UV-VIS spectroscopy analysis showed that the optical absorption threshold of transition metal doped-TiO\(_2\) nanowires was the red-shifted to visible light region compare to the undoped nanowires, indicating promise for visible light photocatalytic and dilute magnetic semiconductor applications.